Corynebacterium imitans isolated from blood culture in a patient with suspected bacteremia - the first isolation from human clinical material in the Czech Republic - JeŽek, Petr; Zavadilová, Jana; Kolínská, Renáta; Švec, Pavel; Guttwirth, Jiří; Petráš, Petr (Klinicka mikrobiologie a infekcni lekarstvi, 2014)
The current view of the clinical importance of nondiphtherial corynebacteria recovered from human clinical material has changed considerably in recent decades; in many cases, a direct etiological role is assumed or has already been demonstrated. Presented is a case of suspected bacteremia in a hospitalized elderly woman with isolation of the very rare species Corynebacterium imitans from blood culture. However, the etiological significance of the isolated microorganism remains unclear. The aim was not to demonstrate the etiological significance of the isolated C. imitans strain but to report the occurrence of this very rare species which is considered to be the first isolation from humans in the Czech Republic.